Proceedings 2018 Network and Distributed System Security Symposium 2018
DOI: 10.14722/ndss.2018.23244
|View full text |Cite
|
Sign up to set email alerts
|

A Large-scale Analysis of Content Modification by Open HTTP Proxies

Abstract: Open HTTP proxies offer a quick and convenient solution for routing web traffic towards a destination. In contrast to more elaborate relaying systems, such as anonymity networks or VPN services, users can freely connect to an open HTTP proxy without the need to install any special software. Therefore, open HTTP proxies are an attractive option for bypassing IPbased filters and geo-location restrictions, circumventing content blocking and censorship, and in general, hiding the client's IP address when accessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Such vulnerabilities of middleboxes have been reported in several studies [8], [11], [46], [34], [44]; for instance, some middleboxes accept nearly all certificates in spite of certificate validation failures, which gives a chance for another compromised/malicious middlebox to meddle in the TLS session [8], [11], [46]. Similarly, a middlebox that splits a TLS session may support only weak ciphersuites, which are vulnerable to known attacks such as the Logjam attack [1] or the FREAK attack [3].…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…Such vulnerabilities of middleboxes have been reported in several studies [8], [11], [46], [34], [44]; for instance, some middleboxes accept nearly all certificates in spite of certificate validation failures, which gives a chance for another compromised/malicious middlebox to meddle in the TLS session [8], [11], [46]. Similarly, a middlebox that splits a TLS session may support only weak ciphersuites, which are vulnerable to known attacks such as the Logjam attack [1] or the FREAK attack [3].…”
Section: Introductionmentioning
confidence: 63%
“…Although SplitTLS complies with the current TLS practice, several studies have reported that some middleboxes fail to correctly validate certificates, degrade to weaker ciphersuites, or insert malicious scripts [8], [11], [44], [5]. This means that fundamental security properties (i.e., authentication, confidentiality, and integrity) between two endpoints are broken.…”
Section: E Security Problems In Splittlsmentioning
confidence: 99%
See 2 more Smart Citations
“…More than 25% of malicious proxies return at least 10 les with malicious content, while the top 10% of malicious proxies return 56 or more malicious les. Surprisingly, none of the 469 discovered proxies that return malicious content ( §7.1) are listed on the service run by Tsirantonakis et al [46] that reports misbehaving proxies. This suggests that correctly identifying misbehaving proxies is very challenging, since proxy misbehavior may be transient and may take di erent forms.…”
Section: Network Diversity and Consistency Of Malicious Proxiesmentioning
confidence: 99%